1990
DOI: 10.1164/ajrccm/141.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilators in Patients with Chronic Obstructive Pulmonary Disease on Mechanical Ventilation: Utilization of Metered-dose Inhalers

Abstract: Bronchodilators are used widely in the acute exacerbations of chronic obstructive pulmonary disease (COPD), although their effectiveness is not clearly established. We used three bronchodilators in 20 patients with COPD who were being mechanically ventilated. Two of the bronchodilators, ipratropium bromide and salbutamol, were administered from metered-dose inhalers (MDI) through an adapter to the endotracheal tube, and the third, aminophylline, was administered in the form of intravenous infusion. Before admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
7

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 14 publications
4
33
1
7
Order By: Relevance
“…A decrease in values of Rrs,max and Rrs,min occurs following bronchodilator administration in mechanicallyventilated patients [11,12,39,41,50].…”
Section: Assessment Of the Bronchodilator Responsementioning
confidence: 98%
See 3 more Smart Citations
“…A decrease in values of Rrs,max and Rrs,min occurs following bronchodilator administration in mechanicallyventilated patients [11,12,39,41,50].…”
Section: Assessment Of the Bronchodilator Responsementioning
confidence: 98%
“…Few investigators have examined the efficacy of bronchodilators in mechanically-ventilated patients [8,11,12,15,[38][39][40][41][42][43][44]. Early studies showed promising results following bronchodilator administration by a MDI [42][43][44], and yet the data were ignored for several years.…”
Section: Efficacy Of Bronchodilator Administered By a MDI In Mechanicmentioning
confidence: 99%
See 2 more Smart Citations
“…The goals of bronchodilator therapy are to reverse bronchoconstriction, decrease the work of breathing, and/or relieve dyspnea. Administration of either aerosolized b-adrenergic (26,29,(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93) or anticholinergic drugs (77,79,83,86) produces significant bronchodilator responses in ventilated patients. The combination of fenoterol and ipratropium bromide was found more effective than ipratropium alone in ventilated patients with COPD.…”
Section: Bronchodilator Therapymentioning
confidence: 99%